Identification of Two Enzymes for Trehalose Synthesis and Their Potential Function in Growth and Development in Peanut (Arachis hypogaea): Genome Analysis of the Encoding Trehalose Synthesis Enzymes in Peanut - Chu, Ha Duc; Tran, Yen Thi Hai; Pham, Chau Thuy; Le, Thi Ngoc Quynh; Tran, Thi Thanh Huyen; Nguyen, Trung Quoc; Dong, Huy Gioi; Tran, Van Tien; Cao, Phi Bang (Journal of Tropical Life Science, 2024)
Plant trehalose has been regarded to play a key role in various biological processes during the growth and development stages. Trehalose-6-phosphate synthase (TPS) and trehalose-6-phosphate phosphatase (TPP) are two important enzymes for the synthesis of plant trehalose. Up till now, the TPS and TPP gene families have been identified and characterized in numerous higher plant species, but are rarely recorded in peanuts (Arachis hypogaea). In this study, a comprehensive search was performed to identify all putative TPS and TPP proteins in the peanut genome using Arabidopsis TPS and TPP proteins as queries. We then analyzed the characteristics of TPS and TPP members, including physic-chemical parameters, subcellular localization, phylogeny relationships, gene duplication, and expression patterns by various computational tools. As a result, a total of 17 ArahyTPS and 15 ArahyTPP genes were identified and annotated in the peanut genome, which was expanded by segmental duplication events. Our Neighbor-Joining based phylogenetic tree indicated that the ArahyTPS and ArahyTPP proteins could be categorized into three and two major branches. Gene structures and protein features analysis exhibited that the ArahyTPS and ArahyTPP proteins shared high structural and functional similarities. Based on previous RNA-Seq datasets, a majority of the ArahyTPS and ArahyTPP genes were found to specifically express in at least one major organ/tissue during the growth and development. This work will not only lead to a solid foundation on reveal the potential roles of ArahyTPS and ArahyTPP gene families in peanuts but also provide evidence to related trehalose research in other higher plant species.